The influence of natural and climatic factors on people living under different climatic conditions - O. V. Aleksandrova; A. D. Afanaseva; Yu. I. Ragino (Сибирский научный медицинский журнал, 2025)
The article presents a review of the literature devoted to the analysis of the influence of natural and climatic factors on the human body. We analyzed the influence of parameters such as ambient temperature, including the effects of heat and cold, as well as fluctuations in atmospheric pressure and humidity levels. A number of studies have demonstrated a significant impact of both increase and decrease in ambient temperature relative to comfort level, and a correlation with atmospheric pressure and humidity has been established. The effects of these factors on the functioning of the cardiovascular, respiratory and nervous systems were considered. Extreme weather can disrupt the body’s adaptive processes, leading to oxidative stress, altered blood rheology, vasospasm or vasodilation, and bronchoconstriction. Depending on fluctuations in relative humidity and atmospheric pressure, the ionic composition of the air may change, affecting the human body. Natural and climatic factors can act as a trigger for the exacerbation of chronic diseases. In conclusion, the vector of possible actions is determined to prevent the occurrence of serious consequences for citizens, the health system, and the economy of the country.